Empirical Determination of Scattering Matrices from Magnetic Molecular Interferometry for Gas–Surface Collisions - Helen Chadwick (The Journal of Physical Chemistry C, 2024)
The rotational orientation dependence of H2 scattering into different diffraction channels on a Cu(511) surface is studied using a magnetic manipulation interferometry technique. For some channels, markedly different signals are measured, whereas for others, they are more similar. The data are analyzed to obtain scattering matrices, which quantify how the amplitude and phase of the wave function change during the gas–surface collision and are extremely sensitive to the underlying potential. Fits to simulated data with noise at levels comparable to those obtained in the experimental data are also presented, which provide an estimate of the error on the scattering matrix parameters that are obtained, with the uncertainties in the values tending to be lower for the higher order diffraction peaks. The results presented here provide extremely stringent benchmarks for the development of accurate theoretical models, with the number of different channels studied reducing the likelihood of an inaccurate model fortuitously reproducing all the data.